2013
DOI: 10.1039/c3dt50969a
|View full text |Cite
|
Sign up to set email alerts
|

Formation in aqueous solution of a non-oxido VIV complex with VN6 coordination. Potentiometric, ESI-MS, spectroscopic and computational characterization

Abstract: The behaviour of the system formed by V(IV)O(2+) ion with all-cis-2,4,6-trimethoxycyclohexane-1,3,5-triamine (tmca) was characterized in aqueous solution through the combined application of electron paramagnetic resonance (EPR) and UV-Vis spectroscopy, electrospray ionization mass spectrometry (ESI-MS), pH-potentiometry and DFT methods. The formation of an unusual non-oxido [V(tmcaH-2)2] species with VN6 coordination, with the ligand in the bianionic form, was demonstrated. The geometry, EPR and UV-Vis spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 113 publications
2
30
0
Order By: Relevance
“…19 The transformation of a V IV into a V IV O species can be followed by EPR spectroscopy. In particular, a significant increase of the highest value of the 51 V anisotropic hyperfine coupling constant, from 95-145 to 155-165 × 10 −4 cm −1 , is observed, in agreement with what is reported in the literature; 38 the results are confirmed by DFT calculations of the 51 V A values (Table 2). We conclude that three of the six V IV complexes convert to…”
Section: Resultssupporting
confidence: 91%
“…19 The transformation of a V IV into a V IV O species can be followed by EPR spectroscopy. In particular, a significant increase of the highest value of the 51 V anisotropic hyperfine coupling constant, from 95-145 to 155-165 × 10 −4 cm −1 , is observed, in agreement with what is reported in the literature; 38 the results are confirmed by DFT calculations of the 51 V A values (Table 2). We conclude that three of the six V IV complexes convert to…”
Section: Resultssupporting
confidence: 91%
“…The parts of curves after a  ~ 1 (end point of MCCh), the longer the higher is the part of vanadyl ion, are evidently connected with VO(IV) – MCCh complexation via the deprotonated hydroxyl groups but not the amine groups. This result is not surprising because it is known that the affinity of V IV O 2+ ion is much higher towards ligands with oxygen donors [27-29]. Coordinative interaction of oxido V IV O 2+ ion towards only nitrogen donors is very low and results in hydrolytic processes in acid and neutral solution.…”
Section: Resultsmentioning
confidence: 93%
“…Nowadays, the prediction of 51 V HFC tensor A is possible through the DFT methods. We recently observed that the ORCA software gives better results than popular Gaussian for non‐oxido vanadium(IV) complexes, because it includes the second‐order spin–orbit effects, whose contribution to A is more important than for V IV O species , , . Among the functionals, it has been recently demonstrated that, for a bare V IV complex, the double hybrid B2PLYP gives a mean percentage deviation (MPD) from A iso of –0.3 % if using the basis set VTZ, and from A i ( i = x or z , depending on the symmetry and electronic structure of the complex) of –0.9 % if using the 6‐311g(d,p) basis set .…”
Section: Resultsmentioning
confidence: 99%